2017
DOI: 10.1038/s41598-017-17083-w
|View full text |Cite
|
Sign up to set email alerts
|

Association of kidney fibrosis with urinary peptides: a path towards non-invasive liquid biopsies?

Abstract: Chronic kidney disease (CKD) is a prevalent cause of morbidity and mortality worldwide. A hallmark of CKD progression is renal fibrosis characterized by excessive accumulation of extracellular matrix (ECM) proteins. In this study, we aimed to investigate the correlation of the urinary proteome classifier CKD273 and individual urinary peptides with the degree of fibrosis. In total, 42 kidney biopsies and urine samples were examined. The percentage of fibrosis per total tissue area was assessed in Masson trichro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 60 publications
(65 reference statements)
3
43
1
Order By: Relevance
“…CKD273 was recently used to predict mortality in individuals with type 2 diabetes and their response to albuminuria treatment . Other examples for the application of multi‐dimensional marker were published , and the application of CE‐MS in urinary peptidomics for the diagnosis of CKD was reviewed recently . Urinary peptidomics by CE‐MS was furthermore used for the identification of biomarkers for chronic obstructive pulmonary disease , diastolic left ventricular dysfunction , end‐stage renal disease , chronic graft‐versus‐host disease , non‐alcoholic fatty liver disease and systemic lupus erythematosus .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…CKD273 was recently used to predict mortality in individuals with type 2 diabetes and their response to albuminuria treatment . Other examples for the application of multi‐dimensional marker were published , and the application of CE‐MS in urinary peptidomics for the diagnosis of CKD was reviewed recently . Urinary peptidomics by CE‐MS was furthermore used for the identification of biomarkers for chronic obstructive pulmonary disease , diastolic left ventricular dysfunction , end‐stage renal disease , chronic graft‐versus‐host disease , non‐alcoholic fatty liver disease and systemic lupus erythematosus .…”
Section: Analytical Applicationsmentioning
confidence: 99%
“…There is evidence that CKD273 can directly reflect early kidney damage, as it is associated with renal fibrosis . This was also demonstrated with the correlation analysis of the baseline data, where CKD273 scores have a strong and significant correlation with eGFR (Figure ), superior to that of albuminuria (data are not shown).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, urinary peptides may be used to diagnose and monitor renal fibrosis. Magalhaes et al [29] showed a significant and positive correlation between the urinary classifier CKD273 and the degree of fibrosis in 42 kidney biopsies, which could not be detected by the serum and urine biochemical parameters routinely used to estimate the severity of CKD. Seven fibrosis-associated collagen fragments displayed a negative association with the degree of fibrosis, which suggests they have a causal relation to the accumulation of extracellular matrix observed in renal tissue [29].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…Magalhaes et al [29] showed a significant and positive correlation between the urinary classifier CKD273 and the degree of fibrosis in 42 kidney biopsies, which could not be detected by the serum and urine biochemical parameters routinely used to estimate the severity of CKD. Seven fibrosis-associated collagen fragments displayed a negative association with the degree of fibrosis, which suggests they have a causal relation to the accumulation of extracellular matrix observed in renal tissue [29]. Interestingly, some CKD-associated abnormalities such as reduction of collagen fragments were found to correlate with aging in adults [30], suggesting a reduced turnover of extracellular matrix promoting fibrosis as a major mechanism of kidney aging.…”
Section: Chronic Kidney Diseasementioning
confidence: 99%